Implementación de Tics y el desempeño laboral del personal administrativo de la UPV - Municipalidad Provincial Sánchez Carrión, 2019-2022. Huamachuco - Roman Monzón, Neicer Nathanael (2023)
The present work entitled: implementation of Tics and the work performance of the administrative staff of the UPV - Provincial Municipality Sánchez Carrión, 2019-2022. Huamachuco's main objective is to propose and implement the use of Information and Communication Technologies, in the MPSC Neighborhood Participation unit, since according to this report, low efficiency was found when preparing support delivery documents, due to ignorance of the use of ICT, another problem was also found, such as excessive documentation when preparing expense reimbursement reports and that both problems affected both the client (user) and the workers. thus increase job performance. For this reason, solutions to these problems will be presented, improving work performance in carrying out these activities, which allowed improving productivity, providing quality service and customer satisfaction, in addition, actions and courses will be needed that will be very useful.